Pengembangan SMK Berbasis Potensi Daerah dan Kebutuhan Tenaga Kerja: Studi Kualitatif di Indonesia - Enjang Suhaedin; Wike Oriza; Ambiyar Ambiyar; Remon Lapisa (Journal on Education, 2024)
This research aims to analyze the development of Vocational High Schools (SMK) based on regional potential and workforce needs in Indonesia. This study explores the relevance of the vocational school curriculum to regional potential and the needs of the local job market, identifies the challenges faced in developing regional potential-based education programs, and analyzes the influence of vocational school collaboration, industry and government on the quality of graduates and employment. The research method used is qualitative, with data collection techniques through in-depth interviews, observation and document analysis. The research results show that the relevance of the vocational school curriculum to regional potential and local workforce needs still varies in various regions, with some vocational schools in urban areas succeeding in adapting their curriculum, while vocational schools in rural areas still face obstacles. The main challenges identified include limited facilities and infrastructure, lack of competent teaching staff, limited collaboration with industry, and suboptimal government support. This research also found that good cooperation between vocational schools, industry and government has a positive impact on the quality of graduates and employment. Based on these findings, this research recommends adjusting the curriculum, improving facilities and infrastructure, training and professional development for teachers, increasing collaboration with industry, and more optimal government support. By implementing these recommendations, it is hoped that vocational schools in Indonesia can develop into quality vocational education institutions capable of producing graduates who are ready to work and are competitive in the global market.